2014
DOI: 10.1182/blood-2013-09-526277
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of the coagulation protease cascade during virus infection

Abstract: The coagulation cascade is activated during viral infections. This response may be part of the host defense system to limit spread of the pathogen. However, excessive activation of the coagulation cascade can be deleterious. In fact, inhibition of the tissue factor/factor VIIa complex reduced mortality in a monkey model of Ebola hemorrhagic fever. Other studies showed that incorporation of tissue factor into the envelope of herpes simplex virus increases infection of endothelial cells and mice. Furthermore, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
208
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 192 publications
(215 citation statements)
references
References 96 publications
3
208
0
4
Order By: Relevance
“…PAR1 or PAR2 activation enhanced the production of inflammatory mediators and cytokines and participated in chronic airway diseases, such as asthma, COPD, and IPF (idiopathic pulmonary fibrosis) (15). Virus infection also activated PAR1 and PAR2 to mediate innate immune, airway inflammation, and lung function (16)(17)(18). We have found that PAR2, but not PAR1, was obviously upregulated in the later stage of RSV infection in our preliminary data.…”
supporting
confidence: 48%
“…PAR1 or PAR2 activation enhanced the production of inflammatory mediators and cytokines and participated in chronic airway diseases, such as asthma, COPD, and IPF (idiopathic pulmonary fibrosis) (15). Virus infection also activated PAR1 and PAR2 to mediate innate immune, airway inflammation, and lung function (16)(17)(18). We have found that PAR2, but not PAR1, was obviously upregulated in the later stage of RSV infection in our preliminary data.…”
supporting
confidence: 48%
“…[1][2][3][4] Blood-borne proteases coordinate hemostatic and innate immune responses through coagulation and complement cascades. 3,5 Under physiological conditions, the coagulation cascade is triggered by exposure of extravascular cells expressing the membrane-bound cofactor tissue factor (TF) to plasma coagulation zymogens upon vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…MVs are particularly prothrombotic when displaying tissue factor (TF) (4). Viruses, such as influenza, induce TF expression in monocytes and endothelial cells and activate the coagulation cascade, which can result in DIC (5). Influenza virus H1N1 also activates platelets and induces the release of MVs (6).…”
Section: Introductionmentioning
confidence: 99%